2015
DOI: 10.1039/c5ra11192g
|View full text |Cite
|
Sign up to set email alerts
|

Largely improved fracture toughness of an immiscible poly(l-lactide)/ethylene-co-vinyl acetate blend achieved by adding carbon nanotubes

Abstract: In this work, different contents of CNTs were introduced into an immiscible poly(L-lactide)/ethylene-covinyl acetate (PLLA/EVA) blend that exhibited a sea-island structure to further demonstrate the toughening probability of CNTs on the immiscible polymer blends. The fracture toughness was evaluated through impact measurements. The impact-fractured surface morphologies as well as the morphological changes of the blend induced by adding CNTs were characterized using scanning electron microscope. Furthermore, rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…The use of inorganic fillers in the elastomer could toughen the polymeric system and further enhance the impact strength of the blends 34–37 . Wang et al reported that the addition of carbon nanotube (CNT) to the PLA/EVA can largely enhance its fracture toughness 34 . CNTs are placed near EVA particles and largely increased the plastic deformation ability of the PLA matrix upon fracture.…”
Section: Introductionmentioning
confidence: 99%
“…The use of inorganic fillers in the elastomer could toughen the polymeric system and further enhance the impact strength of the blends 34–37 . Wang et al reported that the addition of carbon nanotube (CNT) to the PLA/EVA can largely enhance its fracture toughness 34 . CNTs are placed near EVA particles and largely increased the plastic deformation ability of the PLA matrix upon fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Poly­(ethylene- co -vinyl acetate) (EVA) has drawn much attention because of its tunable physical and chemical characteristics. The mechanical properties of EVA are controlled by ethylene/vinyl acetate (VA) weight composition. EVA, with higher VA units, shows rubber property and is always applied to improve the fracture toughness of rigid substrates. , Furthermore, EVA colloids act as host materials for electrolytes because of much of electrolyte permeating into the colloids. Inspired by the merits of PAA and EVA, we report a new binder PAA/EVA prepared by simply mixing low-cost PAA and EVA.…”
Section: Introductionmentioning
confidence: 99%
“…Blending conducting fillers as carbon nanotube (CNT) expands the field of applications of these semi-biodegradable composite as antistatic, dielectric and microwave absorbing materials for utilization in electronic packaging. Most of the studies involving CNT-based PLA/EVA composites focused on the improvement of mechanical properties and toughness of the blends (Shi et al, 2011(Shi et al, , 2012Wang et al, 2015Wang et al, , 2016Liu et al, 2016). Studies related with the electrical properties of PLA/EVA blends loaded with CNT was reported by Shi et al (2013).…”
Section: Introductionmentioning
confidence: 99%